Clinical Manifestations and Pathogenesis of Acute Necrotizing Encephalopathy: The Interface Between Systemic Infection and Neurologic Injury - Shukla, Priya; Mandalla, Abby; Elrick, Matthew J.; Venkatesan, Arun (Frontiers in Neurology, 2022)
Acute necrotizing encephalopathy (ANE) is a devastating neurologic condition that can arise following a variety of systemic infections, including influenza and SARS-CoV-2. Affected individuals typically present with rapid changes in consciousness, focal neurological deficits, and seizures. Neuroimaging reveals symmetric, bilateral deep gray matter lesions, often involving the thalami, with evidence of necrosis and/or hemorrhage. The clinical and radiologic picture must be distinguished from direct infection of the central nervous system by some viruses, and from metabolic and mitochondrial disorders. Outcomes following ANE are poor overall and worse in those with brainstem involvement. Specific management is often directed toward modulating immune responses given the potential role of systemic inflammation and cytokine storm in potentiating neurologic injury in ANE, though benefits of such approaches remain unclear. The finding that many patients have mutations in the nucleoporin gene RANBP2, which encodes a multifunctional protein that plays a key role in nucleocytoplasmic transport, may allow for the development of disease models that provide insights into pathogenic mechanisms and novel therapeutic approaches.